Reactions to "Ag News" Releases: Survey of Idaho Newspaper Editors and Broadcast News Directors - Marlene Fritz (Journal of Applied Communications, 1987)
Communications specialists at the University of Idaho College of Agriculture (UI) surveyed the Idaho media in October 1986 to determine evaluations of "Ag News" releases. Of 166 surveys mailed, 104 were returned (63 percent). Results indicated that the UI news releases were well accepted and rated, at least, "very good." A majority of respondents said the releases were "generally understandable to the public," that the maximum length of a story usually reprinted in full was two pages; and that the news releases were preferable to "tip" sheets for all media except television.